Fatigue Dan Kualitas Hidup Pada Pasien Gagal Ginjal Kronis Dengan Terapi Hemodialisa - Dhea Natashia; Diana Irawati; Fajar Hidayat (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: The aim of this study was to investigate the relationship of fatigue to the quality of life among patients who undergo hemodialysisMethods: A descriptive correlative study with purposive sampling technique was applied in this study. Data obtained from direct observation using the FACIT-F questionnaire and WHOQOL BREF. A total of 80 respondents was recruited.Results:   The results of the study showed the average age of the subject were 47 years, 56% of them were male, and the majority had a high school educational background. Most of the patients had a length of hemodialysis for more than two years. Hemodialysis patients were experienced fatigue with a mean value of 26,50 (SD = 7.07). Among domains of quality of life, the social domain had the lowest score (9.38). Multivariate analysis showed there was a consistent correlation between fatigue and four domains of quality of life.Conclusion:   Fatigue is a major problem experienced by the patient’s hemodialysis and influences their quality of life. The researchers suggest the health services can improve promotive and preventive efforts through education, training, related to fatigue to promote quality of life for clients who undergo hemodialysis, especially female, older age, and lower educational status. Further research is expected to examine the other variables such as social support and environment